Characterizing Pediatric High Frequency Users of California Emergency Departments - Supat, Benjamin (Am J Emerg Med, 2018)
OBJECTIVE: Emergency department (ED) utilization has increased for the last several decades. Despite a focus on adult frequent ED users, little research has examined pediatric frequent ED users. The purpose of this study was to assess pediatric ED utilization in California and to describe those identified as frequent ED users. METHODS: This was a retrospective multi-facility study of ED visits by children 1–17 years of age using statewide data from the California Office of Statewide Health Planning and Development. Patients were classified into utilization groups by the number of ED visits in a one-year period prior to their last visit in 2016: occasional (1–5 visits) vs. frequent (>5 visits). Differences in patient characteristics were compared between occasional and frequent users. RESULTS: There were 690,130 patients between 1 and 17 years of age with 1,238,262 visits during the study period. Children with ≥ 6 visits (2.3%) accounted for 9.3% of all visits. 67% of frequent users had no visits to a pediatric ED. Over forty percent (41.4%) of frequent users visited 2 or more hospitals, compared to 7.7% of occasional users. In multivariate analysis, the characteristics with the largest associations with frequent ED use were age, payer, and being admitted/transferred. CONCLUSIONS: The majority of pediatric frequent users do not seek care in pediatric EDs. Age, prior admission, and Medicare/Medicaid appear to have the largest associations with pediatric patient frequent ED utilization.